2011
DOI: 10.1002/ajp.21006
|View full text |Cite
|
Sign up to set email alerts
|

Historical geographic dispersal of the golden snub‐nosed monkey (Rhinopithecus roxellana) and the influence of climatic oscillations

Abstract: Current understanding of historic climate oscillations that have occurred over the past few million years has modified scientific views on evolution. Major climatic events have caused local and global extinction of plants and animals and have impacted the spatial distribution of many species. The endangered golden snub-nosed monkey (Rhinopithecus roxellana) currently inhabits three isolated regions of China: the Sichuan and Gansu provinces (SG), the Qinling Mountains in Shaanxi province (QL), and the Shennongj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…However, there was also a small Δ K peak at K = 5 (Δ K = 23.59), and results showed that in addition to the divergence between SG and QL, there was also divergence within the SG and QL populations. These results agree with earlier studies, where the differences within the SG and QL populations resulted from their different origins and habitat fragmentation [33,34]. The clear population structure observed in microsatellites was not found at either the DQA1 locus or the DQB1 locus (Additional file 3: Figure S1).…”
Section: Resultssupporting
confidence: 91%
“…However, there was also a small Δ K peak at K = 5 (Δ K = 23.59), and results showed that in addition to the divergence between SG and QL, there was also divergence within the SG and QL populations. These results agree with earlier studies, where the differences within the SG and QL populations resulted from their different origins and habitat fragmentation [33,34]. The clear population structure observed in microsatellites was not found at either the DQA1 locus or the DQB1 locus (Additional file 3: Figure S1).…”
Section: Resultssupporting
confidence: 91%
“…Phylogenetic reconstructions based on mitochondrial DNA data and paleobiogeography indicate that Rhinopithecus diverged from the other genera of odd-nosed monkeys during the late Miocene, and then differentiated into five species48. This appears to have begun ~2 million years ago in response to oscillations in paleoclimate associated with the uplifting of the Tibetan Plateau, a decrease in temperature and rainfall, a reduction in broadleaf and evergreen forest habitats, glacial expansion and geographical barriers that restricted gene flow across populations495051. Although the precise factors that led to the formation of a multilevel society remain unclear, increased environmental heterogeneity and forest fragmentation during periods of glacial maximum may have resulted in feeding sites that were hyper-dispersed across the landscape52.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond genetic drift, a foundation event may have also contributed to the low genetic diversity present in the SNJ population. Among the three populations, the SG population is predicted to be the ancestral population, with the SNJ population arising from the QL population [57]. Microsatellites (unpublished data) and mitochondrial data [57] suggested little gene flow between SNJ and the other two populations.…”
Section: Genetic Variation Of Drb In Golden Snub-nosed Monkeymentioning
confidence: 99%
“…Among the three populations, the SG population is predicted to be the ancestral population, with the SNJ population arising from the QL population [57]. Microsatellites (unpublished data) and mitochondrial data [57] suggested little gene flow between SNJ and the other two populations. This may indicate that the genetic variation in the SNJ population was reduced compared with the other populations either at its foundation or soon after [52].…”
Section: Genetic Variation Of Drb In Golden Snub-nosed Monkeymentioning
confidence: 99%